The synthesis of LA-Fe3O4@PDA-PEG-DOX for photothermal therapy–chemotherapy. Issue 7 (30th January 2018) - Chen, Yuhua; Zhang, Feng; Wang, Qian; Lin, Huiming; Tong, Ruihan; An, Na; Qu, Fengyu
Abstract : The improved cell uptake and the synergistic effect of chemo-/photothermal therapy ensure the enhanced specific cytotoxicity toward HepG2 cells. Abstract : A facile methodology is presented to construct a multifunctional nanocomposite that integrates photothermal therapy and specific drug release into a single nanostructure. Firstly, magnetic Fe3 O4 @polydopamine core–shell nanoparticles (Fe3 O4 @PDA) were synthesized via a reversed-phase microemulsion approach. By varying the amount of DA, Fe3 O4 @PDA with a particle size of 28–38 nm can be obtained. To further ensure the monodispersity, biocompatibility and specific uptake, PEG and lactobionic acid (LA) were grafted onto Fe3 O4 @PDA (LA-Fe3 O4 @PDA-PEG), whose fast photothermal conversion is derived by the combination of Fe3 O4 and PDA with high near infrared (NIR) absorption. Then, doxorubicin hydrochloride (DOX) was adopted as the typical anticancer drug, which was loaded onto LA-Fe3 O4 @PDA-PEG via electrostatic and π–π stacking interaction. The release kinetics investigation further demonstrated the acid/heat-triggered DOX release. HepG2 cells (hepatocellular cell line) were used as the target cancer cells, and the fast uptake was due to the nanoparticle size and abundant asialoglycoprotein receptors on HepG2 cells. Besides, an external magnetic field also can improve the uptake, especially when the magnet is placed at the bottom of the cell disk. The enhanced specific cytotoxicity toward HepG2 cells was also ascribed to the synergistic effect of chemo- and photothermal therapy. Based on the novel properties, the LA-Fe3 O4 @PDA-PEG-DOX nanocomposite showed its potential application in hepatocyte therapy.